POLICY EVALUATION OF THE REMPANG–GALANG GLASS FACTORY DEVELOPMENT FROM SOCIAL AND ENVIRONMENTAL JUSTICE PERSPECTIVES - Nurmasari Nurmasari; Yustina Yustina (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
The development of a glass manufacturing plant within the Rempang Eco City project on Rempang Island, Riau Islands Province, represents the Indonesian government's strategy to promote investment and accelerate economic growth through the National Strategic Project (PSN) framework. Despite its potential to increase investment, create employment opportunities, and strengthen industrial competitiveness, the project has generated social conflict and environmental concerns. This study aims to analyze the policy rationale underlying the Rempang–Galang glass factory development, examine its implications for social and environmental justice, and evaluate the policy using William N. Dunn’s policy evaluation model. This research employs a qualitative case study approach. Data were collected through a systematic literature review of policy documents, reports from government institutions and civil society organizations, and relevant academic publications. The data were analyzed using content analysis based on the theoretical frameworks of social justice, environmental justice, and public policy evaluation. The findings reveal that the Rempang–Galang development policy is primarily driven by economic growth and investment-oriented objectives. Its implementation has led to an unequal distribution of development benefits and burdens, reflected in the risks of community relocation, loss of living space, pressure on coastal ecosystems, and the emergence of agrarian conflicts. Evaluation based on Dunn’s criteria indicates persistent challenges related to equity, responsiveness, adequacy, and appropriateness. The study concludes that a more participatory, equitable, and sustainable development approach is required through stronger protection of local community rights, inclusive environmental governance, and a fairer distribution of development benefits.